Commentary on 2022. The Peruvian State and regional crises: the development of regional movements 1968-1980 - Delgado Estrada, Juan Manuel (2022)
This text is a commentary on the article by David Slater that deals with the regional social movements of Arequipa and Pucalpa in the military government of 1968 - 1980, where he introduces us to the relationship between each of the two phases of that government, its orientation changes in their public policies, especially the economic ones and the ideological difference of each phase. The current situation of the government of Pedro Castillo is presented and compared with the government of Ollanta Humala, its relations with social movements, parties and leftist groups that after being sworn in forgot them as allies, as well as their electoral promises and program. of government of structural change such as proposing a new constitution. We note that Slater wrote that the Velasco government tried to make structural changes but failed to do so by trying to impose it on those they claimed to represent, they tried to modify the economy by creating state companies but they were not in strategic sectors, decades later the governments It seems that de Humala and Castillo not only failed to implement it because they did not have a congressional majority, but also that they did not care to modify their political practices and their government objectives in order to survive before the Peruvian establishment.